Pengaruh Sistem Keuangan Desa, Partisipasi Penganggaran, Dan Pengawasan Terhadap Akuntabilitas Pengelolaan Dana Desa - Ni Putu Nofy Megantari; Ni Putu Ayu Kusumawati (UNHI Press, 2023)
This researcher wants to find out the influence of the village financial system, participation in the establishment, and supervision of the village fund management account in the villages of the north Denpasar sub-district. The population in this study is the Village Chief, Village Secretary, and Head of Finance village in north Denpasar sub-district. The sample from this study amounted to 24 people incude the village raisi, village kotibi, and the financial manager. The sample collection technique used is saturated samples. The results of this research shows that the rural financial system has a positive and significant impact on theaccountability department of rural development, participation in the budgeting has a negative and negligible impact on accountability for village fund management, and control has positive and low impact on rural fund managemet responsibility.